The Realization of Markedness in Grade XI Students’ Recount Texts in Binjai: Systemic Functional Perspective - Reni Supriani; Ening Nanda Rama; Sulhaida Sulhaida; Aprilza Aswani (Journal of Applied Linguistics and Literature)
This study is an attempt to report the findings of the realization of types and the dominant type of markedness in Grade XI students’ recount texts departing from textual function in systemic functional perspective. Qualitative content analysis was utilized as the research design in this study. Writing sheets were utilized as the instruments for collecting the data. The data were in the form of clauses taken from 25 recount texts written by grade XI senior high school student of SMA Negeri 1 Binjai. It was found that there were 1416 clauses appeared. Specifically, both marked theme (MT) and unmarked theme (UMT) were also discovered in the data with the occurrences of MT totaling to 210 (25.70%) and UMT had 607 occurrences (74.30%). It leads to the conclusion that there were 2 types of markedness namely marked theme (MT) and unmarked theme (UMT) found. Then, UMT was discoverd as the dominant type of markedness.